Unconventional Political Campaigns in Romania: Presidential Impeachment Referendum (2007) - Camelia Cmeciu; Monica Pătruț (Styles of Communication, 2009)
Every referendum brings forth a crisis of legitimacy. Traian Băsescu experienced this political situation in 2007 when he was suspended by the Romanian Parliament. Having as theoretical background social semiotics (Kress, van Leeuwen [1996] 2006; van Leeuwen, 2005), our paper focuses on four semiotic systems (represented participants, composition, multimodality, interactive participants) applied to the images produced by the Romanian citizens, who had been “called up” to an unconventional political campaign through a personal production of a digital guerilla. Beyond its mere iconic function, number “322” has an indexical function of pinpointing the MPs who voted for Traian Băsescu’s impeachment. This number constitutes the main reason for the embodiment of these Romanian MPs in pictorial metaphors. Metaphors activate the semiotic system of multimodality because they become a sign of creativity by combining layers belonging to different iconic isotopic clusters. The humour comes from the allotopies (Greimas 1966) created through the surprising interweaving of politicians and animals, fairy-tales characters or evil/ good heroes.